2007
DOI: 10.1159/000100823
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bioactive Peptide, Valyl-Prolyl-Proline (VPP), and <i>Lactobacillus helveticus</i> Fermented Milk Containing VPP on Bone Loss in Ovariectomized Rats

Abstract: Background: Valyl-prolyl-proline (VPP), a bioactive peptide formed during the fermentation with Lactobacillus helveticus LBK-16H (L. helveticus), has been shown to increase bone formation in vitro. The aim of the study was to determine whether VPP and L. helveticus fermented milk prevent bone loss in ovariectomized (OVX) rats. Methods: During the 12-week intervention study, the OVX rats received VPP in water or L. helveticus fermented milk, containing VPP. Sham-operated rats receiving water acted as controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 67 publications
2
34
0
Order By: Relevance
“…paracasei NTU101 or L. plantarum NTU 102 in ovariectomized mice [8]. Narva et al has also demonstrated a similar outcome with the use of fermented milk, valylprolyl-proline, and Lactobacillus helveticus LBK-16H in ovariectomized rats [73]. Finally, Rodrigues et.al showed that synbiotics, in this study a combination of prebiotics (Yacon flour) and probiotics ( Bifidobacterium longum) , increased bone mineral content in rats [51].…”
Section: ) Probiotics and Bone Healthsupporting
confidence: 61%
“…paracasei NTU101 or L. plantarum NTU 102 in ovariectomized mice [8]. Narva et al has also demonstrated a similar outcome with the use of fermented milk, valylprolyl-proline, and Lactobacillus helveticus LBK-16H in ovariectomized rats [73]. Finally, Rodrigues et.al showed that synbiotics, in this study a combination of prebiotics (Yacon flour) and probiotics ( Bifidobacterium longum) , increased bone mineral content in rats [51].…”
Section: ) Probiotics and Bone Healthsupporting
confidence: 61%
“…The data were expressed as the mean±SE (n=3) with vitamin D and calcium reduces serum parathyroid hormone and bone resorption markers as compared with that of isocaloric and isoprotein dairy products in elderly women. Narva et al [46] showed that Lactobacillus helveticus fermented milk prevented bone loss by decreasing bone turnover and increasing the bone mineral density. Thus, kefir assists with calcium absorption through the TRPV6 calcium channel within an in vitro model system, which in turn may affect the attainment of peak bone mass and OVX-induced bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…In an animal study with ovariectomized rats, the group fed with L. helveticusfermented milk significantly prevented bone loss by decreasing bone turnover and increasing bone mineral density [65]. VPP in water could not prevent bone loss and the authors concluded that this might be due to the poor bioavailability of the bioactive peptide in water.…”
Section: Beneficial Effect On Bone Healthmentioning
confidence: 97%